Straight-Linear Equation Learning Design Through Problem Based Learning to Stimulate Junior High School Students' Critical Thinking Skills - Gharitza Zahira Shofa; Tian Abdul Aziz; Lukman El Hakim (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
A preliminary study in a junior high school revealed that students mathematical critical thinking skills in linear equations remain low, marked by learning barriers dominated by concrete-arithmetic reasoning. This study aims to develop a draft instructional design based on Problem-Based Learning (PBL) specifically formulated to stimulate the four indicators of Facione’s critical thinking framework regarding the concept of pure slope. The method used was instructional design research based on the Instructional Development Model (IDM) by Suparman and was limited to the stage of designing the initial draft product. This design was integrated with the “Future Savings” financial context within the worksheets. The results showed that each designed PBL syntax successfully mapped activities that stimulated critical thinking in a systematic manner. The “interpretation” indicator was triggered through problem orientation; “analysis” through the organization of tabular data; a combination of “analysis” and “evaluation” through the investigation of the  ratio in graphs; “inference” through the formal derivation of the gradient value (m); and “evaluation” through visual challenge questions. The study concludes with an initial draft of instructional design designed to serve as a theoretical basis for bridging students’ transition toward formal algebraic reasoning.